RANCANG BANGUN SISTEM INFORMASI PARIWISATA BERBASIS WEB GIS DI KABUPATEN FLORES TIMUR - Theresia Avilia Tonu Herin avilia; Hari Lugis Purwanto; Rini Agustina (Department of System Information, 2023)
Abstract. Flores Timur Regency is one of the regencies that has various tourism and has become a popular place to target the people who live in Flores especially. Tourism data in Flores Timur Regency can be displayed in the form of visual data or information related to geographical features in a region. This system is often known as Geographic Information System (GIS). GIS will display information about places on the surface of the earth, one of which is an indication of the location of tourist objects. The results obtained from GIS for tourism objects in Flores Regency, Timur, are information on the location of tourism objects along with data on their attributes in the form of name, address, route, tourism details, the closest ATM, the nearest, Market and the closest Hotel. Design Design System Tourism Web-Based GIS Tourism in Flores Timur Regency use Model Waterfall. It is hoped that the results that can be concluded from this research are that the system that is created is expected to be used as a promotional media as well as a tourist guide that will make it easier for tourists to plan their own tourism trips in the Regency of Flores Timur.